Preparing for inclusive teaching : meeting the challenges of teacher education reform - Bondy, Elizabeth; Ross, Dorene Doerre (SUNY series in teacher preparation and development., 2005)
"Grounded in the reform effort of a large state university with a history of excellence in teacher education, this book provides teacher educators and institutions with a valuable resource for navigating the choppy waters of reform. Contributors, all involved in the reform process, tell the story of the University of Florida's efforts in the mid-1990s to unify general and special education in its teacher education program. The book examines various aspects of the reform process, explains challenges faced by teacher educators within today's context and particularly within the context of large research institutions, presents strategies leaders use to keep reform on track in spite of challenges, and includes detailed descriptions of the nature and structure of the reformed program. Also included are valuable insights of teacher education experts from other institutions to contextualize the particulars of this reform within the national education and teacher education scenes."--Jacket